Energy spectrum analysis for intense pulsed electron beam - Shen J. Jie; An H. H.; Liu H. Y.; Remnev G. E. Gennady Efimovich; Nashilevskiy A. V. Aleksandr Vladimirovich; Li D. Y. Dongyu; Zhang J.; Zhong H. W. Haowen; Cui X. J. Xiaojun; Liang G. Y. Guoying; Qu M. Miao; Yan Sh. Sha; et al. (2016, 2016)
Title screen